Research Anthology on Artificial Neural Network Applications 2022
DOI: 10.4018/978-1-6684-2408-7.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Modelling of ANN

Abstract: An artificial neural network (ANN) is an information processing modelling of the human brain inspired by the way biological nervous systems behave. There are about 100 billion neurons in the human brain. Each neuron has a connection point between 1,000 and 100,000. The key element of this paradigm is the novel structure of the information processing system. In the human brain, information is stored in such a way as to be distributed, and we can extract more than one piece of this information when necessary fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The ANN model, which is adapted based on brain behavior, performs in two stages, (i) obtaining knowledge from the environment via a learning procedure and; (ii) using the interneuron link to gather the obtained knowledge (Haykin 2004;Patel et al 2022). The whole process consists of five phases: choosing the input dataset, choosing a proper framework, neural network designing, the process of training and testing, and lastly, model evaluation (Sahoo and Jha 2013).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…The ANN model, which is adapted based on brain behavior, performs in two stages, (i) obtaining knowledge from the environment via a learning procedure and; (ii) using the interneuron link to gather the obtained knowledge (Haykin 2004;Patel et al 2022). The whole process consists of five phases: choosing the input dataset, choosing a proper framework, neural network designing, the process of training and testing, and lastly, model evaluation (Sahoo and Jha 2013).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…Osman et al's (2021) study showed that the Xgboost model had the best results among other used AI-based models such as ANN and support vector regression to predict GWL. A brief detail of studies regarding applying the AI-based models for GWL prediction is presented in The ANN computational approach is biologically inspired by the human brain (Patel et al, 2022). This model seems like the brain in two phases: (a) knowledge is obtained by the network from its environment as a result of a learning procedure, and (b) interneuron connection strengths are used to collect the obtained knowledge (Haykin 2004).…”
Section: Introductionmentioning
confidence: 99%